Ozonation as an Environmentally Friendly Method to Decolorize the Leather Products. (2nd November 2017) - Onem, Ersin; Yorgancioglu, Ali; Namirti, Gamze; Perincek, Seher; Basaran, Bahri; Duran, Kerim
ABSTRACT: In this study, ozonation as an environmentally friendly bleaching method was studied for decolorization of leather products. The effect of ozonation time (3, 5, 10, 15 and 30 min) and water pick-up value (WPV) (0%, 20%, 40%, 60%, 80% and 100%) were investigated on decolorization effect. For this aim, the color measurement and tensile strength tests were performed, and also structural changes were determined by scanning electron microscope (SEM) and Fourier transform infrared spectroscopy (FTIR) after ozonation process. The results of color measurements showed that 30 min for ozonation and 60% WPV were optimum parameters to obtain maximum decolorization effect. SEM images of the ozonated leathers showed some deformations on the collagen fibers and resulted with the slightly decreases in tensile strength of the products. On the other hand, decreases in the tensile strength values were not statistically important levels.